A study on assessment of disability associated with common mental disorders in the slum population of Indore - Ritesh Upadhyay,; Ruchi Soni,; Apurv Thakur,; Dandotiya, Dileep (Asian Journal of Medical Sciences, 2022)
Background: Changing life styles have increase chance of common mental disorders (CMD) which may lead to disability. Aims and Objectives: The aim of the study was (1) to assess CMD in urban slum community and (2) to gain attention of policy makers toward the mental health and its need of the community to address unmet care. Materials and Methods: A crosssectional study was conducted in which 423 people were screened with the help of a pretested questionnaire by Self Reporting Questionnaire (SRQ-20). All the subjects who scored 7 and more in SRQ-20 were further evaluated using Sheehan disability scale. Results: Out of 423 subject, 76.12% reported typical response within 7 in SRQ-20 scoring. Common mental disorder was found in 16.07% with SRQ-20 scoring between 7 and 13. Severe distress was found in 7.80% of the population with SRQ-20 score >14. Among psychological distress group, females scored higher with 10.63%. In the severe distress group, again females scored higher with 4.96%, although this was not statistically significant. A total of 101 subjects were found to have CMD after screening the population and its prevalence come to 238.77 per thousand. Mild disability was found in 59.41% of the people with CMD and 34.65% moderate disability and 5.94% reported severely disability, which was not statistically significant. Conclusion: On the basis of our study findings, we conclude that their mental health requires attention, which is an essential part of an individual’s health. It is essential to design intervention that aim at allaying their distress which can improve their mental health, however, being of a descriptive nature and the study population coming from only one slum the above mentioned finding cannot be generalized.